Niat Melakukan Whistleblowing Kecurangan Akademik: Moralitas Individu dan Pemahaman Tri Pantangan - Dewi Kusuma Wardani; Isti Farin (Universitas Batanghari Jambi, 2023)
This study aims to determine the effect of individual morality and understanding of Tamansiswa’s tri taboo teachings on the intention to commit whistleblowing for academic fraud. This type of research is quantitative research. Data collection in this study used primary data by distributing quetionnaires via Google form to respondents. The population in this study were accounting students at the Tamansiswa University of Yogyakarta and the samples obtained were 125 respondents. The sampling technique used is convenience sampling. The independent variables in this study are individual morality and understanding of Tamansiswa’s tri taboo teachings, while the intention to do whistleblowing is the dependent variable. The results of this study explain that individual morality and understanding of the tri taboo teachings of tamansiswa have a significant effect on the intention to whistleblowing on academic fraud, and individual morality has a positive effect on the intention to commit whistleblowing, understanding of the tri taboo teachings of tamansiswa has a positive effect on the intention to do whistleblowing on academic fraud.